(untitled) (Itinera, 2017)
This study will focus on analyzing the content of the texts of some monosensory performances. Through this research we will discuss how the performance is perceived by the audience. The dominant direction chosen by the artist for his/her performance, does it always correspond to that used by the spectator ? Is there an association of senses that can be established by a monosensory performance ? How cultural and sociological connotations of senses used for this or that performance contribute to a critical interpretation of performance?